SOCIO-ECONOMIC COST ACCOUNTING: A LITERATURE REVIEW - Professor, Suhail Abdullah Al-Tamimi; Lecturer, Hind Shafeeq Nimr; Lecturer, Majid Ahmed AL Anssari (Scholars Digest Publishing, 2024)
This study provides a survey of several recent studies which have focused on socio-economic costs and dealt with the uses of socio-economic cost accounting. The results of the survey showed that accountants have encountered difficulties and challenges in the emerging field of socio-economics cost accounting. In particular, the issue of recording potential future obligations as a result of the damage that entities will cause to society. There is a persistent need to clarify different accounting methods which are made for tackling the negative effects on others because of entities practicing their economic activities, along with attaining social and economic welfare. Future studies examined in this study agreed that socio-economic accounting needs a new conceptual framework that satisfy the needs of all categories of users of financial statements. It must be extrapolated by focusing on the social effects of conditions, the economic reality and technical accounting procedures. The objectives of accounting for socio-economic costs were also embodied in applied studies, through methods of calculating socio-economic costs, monitoring, and evaluating the socio-economic performance of entities.
Keywords: Socio-Economic, Cost Accounting, Welfare, Financial Statements and Economic Activities.